The Existence of Subak in The Legal Politics of Development Program in Bali - Kadek Sarna (Kertha Patrika, 2021)
This study aimed to analyze the legal policies of Bali regionaldevelopment planning in providing protection for the existence ofSubak sustainability in development. This study employed anormative legal research method with a statutory approach, andanalytical conceptual approach. The results indicated that theexistence of Subak has been recognized as a model of managementirrigation in Bali that has been inherited by ancestors, which isprotected by the 1945 Constitution. However, the direction ofregional development planning within the framework ofautonomy, places the agricultural sector as the preferredgovernment affair of the regional government authority. Hence, itcauses the agricultural sector does not become the leading sectorin development planning, and beside the priority of theagricultural budget from the portion of planning and regionaleconomic development, which is still below 2% (two percent).There are also a lack and difficulties in synergizing regionaldevelopment in agriculture with efforts to protect Subaks acrossdistricts/cities in the province of Bali.